Jenayah Rasuah Di Agensi Penguatkuasaan Undang-undang Di Malaysia : Satu Analisis Persepsi Pegawai Awam Di Unit Pencegah Penyeludupan Negeri Kelantan - Mohamad Fauzi, Hj. Husin (2001)

(untitled)
This research was conducted for purpose of analyzing " Corrupt Practices In The Law Enforcement Agencies In Malaysia. The Analysis Is On The Perception Of The Public Officers Of Kelantan Anti-Smuggling Unit", that is the Special Task Force originated by National Security Council. The subject matter of this research of all staff and officers of the said agency of about 200 respondents. This study was carried out by quantitative method whereby one set of modified questionnaires from Social Economic Research Unit (SERU 1991) were distributed to respondents in two parts. The first part consists of personal particulars and the second part consists of the perceptions and values towards corrupt practices, factors contributing to government officers involved in corrupt practices, level of understanding towards the possibilities to report and give information on corrupt practices and to what extent they agree on steps taken to fight corruption effectively. This research was also conducted for the purpose of determining specifically the connections between various chosen factors namely age, level of education, monthly income, original departments, length of service and reason they were placed in that particular position, among respondents with the perception towards their knowledge, awareness, seriousness, willingness and responsibilities as a government officers towards type of corruption (offences) and punishments for corrupt practices and steps taken in combating corruption. Analysis of Variance (ANOVA), Chi-square Test and T-Test were used to analysis information obtained during this study. This study conclude that factors such as age, level of education, monthly income, original departments and reasons they were placed in that particular position did not contain any distinct significant with their perceptions regarding knowledge and awareness towards type of offences and punishments for corrupt practices under Prevention Corruption Act 1997. Results from this research that factors such as level of education, original departments and reason they were placed in that particular position had a significant link with factors caused government officers in combating corruption. Results from this research also shows there is a significant link between factors such as monthly income and level of awareness and their responsibilities to report and give information on corrupt practices. Lastly, it is found that there is no significant link between factors such as age, level of education, monthly income, original departments and reasons they were placed in that particular position with the extent of the seriousness and willingness among respondents to fight corruption. On the whole, results from this research shows that knowledge and awareness of the respondents towards the type of offences and punishments for corrupt practices under Prevention Corruption Act 1997 was still lacking. Also, the extent of their seriousness and willingness among respondents to fight corruption, did not show that they are a dedicated government officers. It can be summarized that this study can at least be used as an instrument in prevention of corruption in this country.